O004 Circadian and behavioural impacts on salivary cortisol during simulated nightshifts. (9th November 2022) - Grosser, L; Yates, C; Dorrian, J; Centofanti, S; Heilbronn, L; Wittert, G; Kennaway, D; Coates, A; Gupta, C; Stepien, J; Matthews, R; Catcheside, P; et al.
Abstract: Introduction: Cortisol regulates multiple body systems and displays a distinct circadian rhythm. Nightshift disrupts this rhythm likely disturbing physiological processes regulated by cortisol. The cumulative effect of consecutive nightshifts, and eating during nightshift, on cortisol is unclear. This study aimed to determine the impact of four-consecutive simulated nightshifts with varied eating conditions at night on salivary cortisol. Methods: N=52 healthy non-shift-working individuals (29-male, 23-female, 24.5±4.8-years; BMI 24.22±2.48 kg/m2) completed four-in-lab consecutive nightshifts (N1-4 2000h-0530h). Participants were randomly assigned to meal-at-night (n=17), snack-at-night (n=16), or no-food-at-night (n=19) conditions. Saliva was collected across 15-time-points between 2000h-0530h per-nightshift. Mixed-effects ANOVAs tested for fixed-effects of night, time, condition, and their interactions on cortisol, and cortisol area under the curve, ground, and increase (AUCg, AUCi), post-meal-snack and the diurnal-cortisol rise (0300h-0530h). Results: Nightshifts produced significant effects of time and night*time (p<0.001), whereby cortisol levels at 2000h increased and levels at 0530h decreased on each consecutive nightshift. Post-food-intake revealed significant effects of condition and night respectively (AUCg; p<0.001; AUCi; p<0.001) with higher levels in meal and snack conditions vs. the no-meal-condition. There were significant effects of night*time*condition (p=.029) on the diurnal-cortisol rise with greater decreases in the meal and no-meal-conditions with each consecutive nightshift Discussion: These results support that nightshift and eating during the nightshift significantly alter daily cortisol rhythms. Such changes may exacerbate shift-work-related alterations to physiological systems influenced by cortisol. Further research is needed to better understand the relationships between altered sleep/wake cycles, meal-timing, and cortisol rhythm changes on cortisol-regulated health outcomes in shift-workers.